Yoga Untuk Meringankan Tingkat Kecemasan Ibu Hamil - Fatihatul Hayati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
Anxiety and fear experienced by mothers especially primipara can extend the duration of labor and increase the incidence of labor by action, namely labor with cesarean section (OR 26.9 CI 95%) and vacuum extraction (OR 4.5 CI 95%). Felman et al also found that more than 12% of mothers who had given birth said that they experienced anxiety during childbirth where these experiences were unpleasant times in their lives. Anxiety will be felt differently during pregnancy and third trimester anxiety is higher than the previous trimester. Pregnancy with anxiety will affect the intrauterine environment and fetal development. Anxiety has an opportunity to increase fear three times in labor and a 1.7 times chance to increase the incidence of cesarean. Mental health including pregnancy anxiety has been proven to be reduced or eliminated through physical exercise. One of the recommended physical exercises is yoga because it is low cost, easy to do and very beneficial for physical fitness and psychology. Yoga in pregnancy is more effective in reducing anxiety and depression